Synergistic effects of photoinduced electron transfer and heavy atom effect based on BODIPY for efficient triplet photosensitizers. (December 2021) - Lee, Jae Moon; Park, Jeong Min; Lee, Hyun Kyu; Kim, Hong Mo; Kim, Jae Hyuk; Kim, Jae Pil
Abstract: Achieving a long triplet lifetime and a high triplet quantum yield for efficient triplet sensitizers are crucial for commercializing triplet–triplet annihilation–upconversion (TTA-UC). Although many donor-acceptor (D-A) or heavy atom-based triplet sensitizers have been extensively studied, each strategy suffers from major drawbacks, such as low triplet quantum yield of D-A and short triplet lifetime of heavy atoms. Herein, we propose the integration of a donor-acceptor with a heavy atom, which improves both triplet lifetime and quantum yield because of the simultaneous utilization of photoinduced electron transfer and the heavy atom effect. To prove this, we synthesized Triphenylamine(D)-BODIPY(A)-bromine(H) (AM6, AM7, and AM8), which were compared with standards such as Triphenylamine(D)-BODIPY(A) (AM2) and BODIPY-Bromine (AM9). The donor-acceptor-heavy atom (D-A-H) compounds (AM6, AM7, AM8) exhibited excellent TTA-UC emission efficiency (3.9–6.5 %), which were high compared to AM2 (1.5 %) and AM9 (1.7 %). Moreover, threshold intensity (Ith ) of AM6, AM7 and AM8 were lower (176–465 mW/cm 2 ) than AM9 (1, 916 mW/cm 2 ), even though they had heavy atom. This demonstrates that D-A-H is an effective molecular design for triplet sensitizers with a synergistic effect. Graphical abstract: Image 1 Highlights: ● D-A-H compounds exhibit better triplet properties than conventional strategies ● Synergistic effect of photoinduced electron transfer and heavy atom effect ● D-A-H compounds overcome the limitation of heavy atom effect